A Survey on Secure Crypto-Biometric System using Blind Authentication Technique - Naik, Anil S; Metagar, Shivappa M; Hasalkar, Praveenkumar D (International Journal of Computer Sciences and Engineering, 2014)
Reliable user authentication is becoming an increasingly important task in the Web-enabled world. Biometrics-based authentication systems offer obvious usability advantages over traditional password and token-based authentication schemes. However, biometrics also raises some issues in lack of privacy, template security, and revocability. The use of cryptographic primitives to bolster the biometric authentication system can solve the issues in biometric system.The combination of biometrics over cryptography may lead to a problem of lack of accuracy in biometric verification. In this paper, We propose a cryptographic protocol for biometrics authentication without revealing personal biometrical data against malicious verifier the protocol is termed as blind biometric authentication protocol, which addresses the concerns of userï¿½s privacy, template protection, trust issue. The accuracy problem can be solved by designing a classifier. The protocol is blind in the sense that it reveals only the identity, and no additional information about the user or the biometric to the authenticating server or vice-versa. The proposed protocol is secure to different attacks.